Use of thermography on roofing performance for rural constructions - Akamine, Luana Alves (2019)
Roof coverings are responsible for promoting a suitable environment for animal production, in addition to be one of the main factors interfering with heat transfer. In this context, this study aimed to assess different roof covers over reduced-scale shed prototypes through thermography. The experimental design was completely randomized with five treatments (TT, thermal; RT, recycled (Tetra Pak); ACT, asbestos-cement; BT, bamboo; and AT, aluminum tile) and 14 repetitions, one for each assessment day. For roofing thermal analysis, thermographic images were taken by a thermographic camera (FLIR® TR420), which measured surface temperature changes (external and internal) at 8:00, 10:00, 12:00, 14:00 and 16:00 h, over 14 days. Environmental temperature was measured inside each prototype. BT roofing showed to be efficient, with values of intermediate surface temperatures, enabling its use in replacing RT, AcT and AT roofing tiles. These other tiles had no difference from each other and showed the worst performances.